CONTROL RECONSTRUCTION OF THE HOMELESS CHILDREN AS THE IMPACT OF URBAN DEVELOPMENT IN LAW PERSPECTIVE (A Study in Samarinda) - Isnawati Isnawati (Jurnal Pembaharuan Hukum, 2018)
Homeless children as a social issue, especially in urban society, in the view of experts and related the organization and departments do not have a uniform similarity of opinion or definition for that matter. In this context, home less children are seen as a social Clearly a social problem that requires an Appropriate methods of settlement in accordance with the expectations of all stakeholders. The research method used a sociological Juridical approach by solving research problems using the data consisting of legal secondary materials or legal regulations used to implement the data to primary data. The results of the research are: 1) Factors that can influence the municipal government in tackling the problems of children who are abo ve the social environmental factors, the Community Culture, the Migration Factor The three factors are the reality that can not be avoided by the city g o v e r n m e n t t h a t will c a u s e t h e c hild homeless children in Samarinda City. 2) The legal Efforts undertaken by the municipality in a different context from the development undertaken by the Samarinda City Regulation No. 16 of 2002 are not yet applicable, with the improvement of the Samarinda City Regulation No. 7 of 2017 the which is implemented a development w ith the current realities